Electrochemical surface treatment of manganese stainless steel using several types of deep eutectic solvents. (September 2021) - Kityk, A.; Hnatko, M.; Pavlik, V.; Boča, M.
Graphical abstract: Highlights: Anodic treatment of stainless steel in DESs take place under diffusion control. The rate of electrodissolution decreases in a row Ethaline - Glyceline – Reline. Electropolished surfaces show increased gloss, hardness and corrosion resistance. Abstract: The use of deep eutectic solvents in the electrochemical treatment of the surfaces of manganese stainless steel has been demonstrated for the first time. The comparative characteristics of Ethaline, Glyceline and Reline, choline chloride based deep eutectic solvents, are examined in this work. It is proved that the process of anodic treatment of the manganese stainless steel in these electrolytes takes place under diffusion control and is characterized by selective dissolution of Fe. Moreover, it was shown that the anodic processing mechanism for Mn-containing stainless steel does not differ between electrolytes. At the same time, however, it was found that the process of anodic dissolution of stainless steel in Ethaline, Glyceline and Reline proceeds at noticeably different rates, due to the different physicochemical properties of these electrolytes. Special attention was paid to the surface characterization of stainless steel samples electropolished in Ethaline, Glyceline and Reline .